The impact of information technology on the design of modern hotels - Al sheikh, Ramzi; armanazi, Zeina (Latakia University Journal -Engineering Sciences Series, 2019)
تأثير تكنولوجيا المعلومات على تصميم الفنادق الحديثة رمزي الشيخ زينة ارمنازي انعكست الثورة الرقمية على العمارة شأنها في ذلك شأن باقي المجالات العلمية والحياتية والاجتماعية. وبرز ذلك في تصميم الفنادق أحد أهم المنشآت العامة لأهميتها الاقتصادية والاجتماعية والحضارية, حيث أن التقنية أدت لفقدان السيطرة على بعض العوامل الهامة في التصميم وأدت لتغيير كبير في مهام وشخصية بعض المباني " ومنها الفنادق ", حيث بدأت محاولات لإيجاد سمات وأدوات تساعد على إعادة السيطرة على العوامل المؤثرة بالتصميم . من هنا تأتي أهمية إبراز التحولات - بفعل تكنولوجيا المعلومات - في التصميم المعماري لمواجهة مشكلة وجهت عمل الباحثين للوصول لنموذج متطور يأخذنا للمرونة في التصميم ليساعد على توازنه من جهة وقابليته للتطور من جهة اخرى حيث يسعى البحث إلى التعرف على دخول التقنيات الحديثة إلى التصميم المعماري للفنادق الحديثة وفق مجموعة من الأسس بدءا" من التطور التاريخي للعمارة الرقمية وانتهاء بالشكل والوظيفة فالمتوقع أن يشمل التغيير مكونات العمارة الرئيسية الثلاث الوظيفة والشكل والإنشاء, ثم يستعرض مجموعة من الحالات الدراسية ويخلص البحث إلى مجموعة من النتائج . The digital revolution has been reflected In architecture which is a continuation of the scientific, life and social fields ,this was highlighted In the design of hotels, one of the most important facilities of general economic , social and cultural importance , as the technology led to the loss of control of some important factors on the design and led to a significant change in the functions and personality of some buildings , including hotels, where attempts to begin to find features and tools to help regain control of the factors affecting the design . Hence the importance of highlighting the transformations caused by information technology in the architectural design to face the problem of the work of researchers to reach a developed model takes us to flexibility in design to help balance of the one hand and its ability to develop of the other . Where the research seeks to identify the entry of modern technology to the architectural design of modern hotels according to a set of foundations from the historical development of digital architecture to the form and function is expected to include the change the components of the three main architecture function, form and construction ,the review a rage of cases ad concludes search for a set of results .